Mathematical Reasoning Ability and Learning Independence of High School Students Through Problem Based Learning Model - Putra, Purnama; Ikhsan, M. (Universitas Malikussaleh, 2019)
The ability of students to answer mathematical reasoning questions and to learn independence is still low. Mathematical reasoning and learning independence are important possessed by students. Therefore, a learning model of a relevant. One of the learning approaches is the Problem Based Learning (PBL) model. The purpose of the study to find out: Differences in the increase in mathematical reasoning abilities and student learning independence taught by using PBL with students taught with conventional learning in terms of (a) all students, and (b) student level (high, medium, low). This research is an experimental research design with a pretest-posttest control group design. The population of this study was all students of class X of the Delima 1 High School in Pidie. While the sample consisted of two classes, namely the experimental class (X-2) and the control class (X-3) taken by random sampling. The instrument used to obtain research data is a test of mathematical reasoning ability and student learning independence. To see the difference in mathematical reasoning abilities and student learning independence between classes PBL models with conventional classes using the t-test. The results showed that the improvement of students' mathematical reasoning abilities and student learning independence that obtained learning with PBL approach was better than students who obtained learning with conventional approach in terms of overall and initial abilities of students (high, medium, low), in quality there were significant differences between students who studied using PBL model with those using conventional learning.